Dini ya Roho
Shelf no.
Religion of the spirit.The disciples of this religion wear a red cro ss on a white gown and carry a cross- staff.This man once had a paranol d psychosis nand his schizophrenic son was a patient in Mathari Hospita l.
AR/MAK PHOTOS/21/6
English
Keywords: Photos of Kenya